Employee Perception on Green Human Resource Management Practices of Selected Firms in the IT Sector: An Empirical Study - Thomas, Fr. Jais V; Kumar, Dr. Aakash (The journal of contemporary issues in business and government, 2022)
As the corporate world is going worldwide, the business is encountering a shift from a conventional financial structure to a modern capacity-based economy which is ready to explore green economic facets of business. Today, Green Human Resource Management (GHRM) has become a key business methodology for the critical associations where Human Resource Departments have a functioning influence in practicing environmental awareness at the workplace. The purpose of this study is to examine the perception on Green Human resource Management among different levels of IT employees from various organizations in Bangalore City. A combination of quantitative and qualitative research methods are employed to gather information. Specifically, data are collected from 155 employees in selected firms in Industry. Study revealed that there is significant relationship between Recruitment and Selection, Training &Development, Performance Appraisal &Rewards in Human Resource Management Practices of selected companies in the IT industry.